JOB SATISFACTION AND TEACHER’S EMPLOYEE ENGAGEMENT OF STATE VOCATIONAL HIGH SCHOOLS - Asikin, Iin; Murni, Sylviana; Akbar, Ma’ruf (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
Employee engagement is very important to drive creativity and ensure people are actively involved in their work. Highly engaged employees are passionate about and influence their to apply additional discretionary effort to their work. The research aims to examine the affect of job satisfaction on employee engagement teachers of state vocational high schools. This study uses a quantitative method with a survey approach and uses the sample from 118 teachers (data were collected by personal distribution) in 4 state vocational High Schools in Depok City, West Java Province, who is selected by using Slovin formula. The result of the study reveals that there is a positive effect the job satisfaction on the employee engagement of state vocational high school teachers. The study concludes that organization must pay attention to their employee’s job satisfaction because when the employee is satisfied, their employee’s engagement will increase.